Intelligence and culture: an introduction. Issue 4 (7th June 2022) - Yelamos, Charlotte; Goodman, Michael S.; Stout, Mark
ABSTRACT: This special issue presents a breadth of scholarly work on the relationship between intelligence and culture. There are several cultural pathways to approach intelligence – the culture of intelligence, being the internal culture of intelligence bodies; intelligence and culture, being how the intelligence community works outwardly with cultures; and intelligence in culture, considering how intelligence is portrayed outside of its own community. This collection of papers covers themes of technological change, language and education, theatre, and literature, all covering a range of historical periods and nationalities that together form a well-rounded and comprehensive understanding of culture in intelligence studies.